AGV scheduling algorithms for container ports - Lim, Hyun Jeong (2019)
With increasing seaborne trade and increase in the traffic in container terminals, it has become important to reduce the vessel turnaround time. The vessel turnaround time can be reduced by reducing the delays that occur at various stages of the loading/ unloading operations. The delays are affected by the availability of quay cranes used for loading/ unloading the containers, and the AGVs that are used to transport the containers. This project aims to explore various scheduling and dispatching algorithms to find ways to reduce these delay times, and thus reduce the vessel turnaround time. A java simulator was created to test various scheduling algorithms and evaluated to determine which is a better algorithm.